ANALISIS STRATIGRAFI SIKUEN RESOLUSI TINGGI FORMASI CIBULAKAN, SUNGAI CIPAMINGKIS, SUKANAGARA, JONGGOL, BOGOR, JAWA BARAT - Edwin, Eric
Cibulakan Formation is located in Bogor Trough has been proven to produce hydrocarbon. Reservoir characterization through multiple approaches, such as outcrop analysis to obtain geometry, thickness, and spatial variation is needed for more comprehensive field development. This study is focused on static reservoir characterization through facies and architectural facies analysis, sequence stratigraphy analysis, and diagenesis analysis. Based on measuring section, 1:80 scale stratigraphic column analysis, sample and thin section analysis, Cibulakan Formation in the research section consists of 14 facieses (A1, A2, B1, B2, B3, C1, C2, C3, C4, C5, D1, D2, and D3) with quartz, feldspar, and foraminifera as the main grain composer. These facieses are part of Shelf (A), Transition (B), Lower Shoreface (C), and Upper Shoreface (D) architectural facieses. Granulometry analysis shows that bathymetry, bioturbation, storm, and slump are affecting grain size distribution significantly. Benthic foraminifera analysis shows that research section bathymetry is inner neritic to bathyal. Diagenesis analysis shows that lithology in the research section is affected by some diagenesis processes, such as: bioturbation, compaction, cementation, and dissolution. Diagenetic environment is interpreted through cement morphology in thin section shows that research section has undergone marine phreatic, meteoric phreatic, mixing zone, and burial environment. The first research section consists of 3 sequences and the second one consists of 4 sequence. Each sequence can be divided into highstand systems tract (HST 1-1, HST 2-1, HST 1-2, HST 2-2, dan HST 3-2), lowstand systems tract – transgressive systems tract (LST– TST 2-1, LST–TST 3-1, LST–TST 1-2, TST 2-2, dan LST–TST 3-2), and falling stage systems tract (FSST 2-1, FSST 2-2, dan FSST 4-2). Planktonic foraminifera analysis shows the age of Cibulakan Formation in the research section is N14–N16 (Middle Miocene – Late Miocene).